(untitled) (Community Based Medical Journal, 2026)
Suicidal hanging constitutes a significant proportion of medicolegal autopsies in Bangladesh, yet region-specific epidemiological data from tertiary care hospitals remain limited. Understanding the demographic and circumstantial patterns of these fatalities is crucial for developing targeted prevention strategies. The objective of this study was to analyze the forensic and epidemiological characteristics of suicidal hanging cases autopsied at a tertiary care hospital in Bangladesh. This prospective cohort study was conducted in the Department of Forensic Medicine at Sir Salimullah Medical College, Mitford Hospital, Dhaka, Bangladesh, from January 2025 to December 2025. A total of 61 cases of suicidal hanging were selected using a purposive sampling technique. Data were collected from post-mortem examination reports, inquest reports, and interviews with family members and were analyzed using SPSS version 23.0. The study found that suicidal hanging was most prevalent among young adults aged 21-30 years, with a male predominance (male-to-female ratio of 1.8:1). The majority of victims were married (62.3%) and from lower socioeconomic backgrounds (59.0%). Hanging was most commonly performed using a soft ligature (75.4%), with a fixed point of suspension (91.8%), and a complete suspension type (73.8%). Financial problems (29.5%) and family disputes (26.2%) emerged as the leading predisposing circumstances. In most cases (85.2%), suicide notes were not left by the deceased. Suicidal hanging in this Bangladeshi cohort primarily affects younger, married males facing socioeconomic stressors. The findings underscore the need for targeted mental health support, crisis intervention, and financial counseling to mitigate suicide risk. CBMJ 2026 July: Vol. 15 No. 02 P:230-238